1993
DOI: 10.1002/etc.5620120604
|View full text |Cite
|
Sign up to set email alerts
|

Fate of linear alkylbenzene sulfonate in the environment

Abstract: An extensive monitoring study was conducted to determine the fate of linear alkylbenzene sulfonate (LAS) during wastewater treatment and in the environment. Results showed that LAS was highly removed during activated sludge (99.3 ± 0.6%), lagoon (98.5 ± 1.8%), oxidation ditch (98.0 ± 4.2%), and rotating biological contact (96.2 ± 6.1%) treatment, with poorer removals observed at trickling filter (77.4 ± 15.5%) facilities. Concentrations of LAS in anaerobically digested sludge (10,462 ± 5170 μg/g) were one to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
2
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 21 publications
8
90
2
1
Order By: Relevance
“…These values correspond very well with other published data for primary sludge (Bema et al 19989;Giger et al 1989;de Henau et al 1989;McAvoy et al 1993). The 'solids effect is still noticeable in the subsequent sampling day as an LAS concentration of 1020 ug/g was measured.…”
Section: Settled Sewagesupporting
confidence: 92%
“…These values correspond very well with other published data for primary sludge (Bema et al 19989;Giger et al 1989;de Henau et al 1989;McAvoy et al 1993). The 'solids effect is still noticeable in the subsequent sampling day as an LAS concentration of 1020 ug/g was measured.…”
Section: Settled Sewagesupporting
confidence: 92%
“…Holt et al, 1995;Holt et al, 1998;Waters and Feijtel, 1995) and in rivers (e.g. McAvoy et al, 1993;Whelan et al, 1999;Fox et al, 2000;Eichhorn et al, 2001;Eichhorn et al, 2002; (Holt et al, 1995). A removal rate for LAS in WWTPs was assumed to be 98% which is appropriate for activated sludge type plants (Holt et al, 1995), the dominant type of treatment technology currently being deployed across China (e.g.…”
Section: Application To Chinamentioning
confidence: 99%
“…Detergent surfactants are complex organic chemicals where hydrophilic and hydrophobic groups are joined together in the same molecules (Huang et al, 2000). There are various types of surfactants used in detergents formulations; the linear alkylbenzene sulfonate (LAS)-ionic surfactants is the most widely used (McAvoy et al, 1997). It was introduced as biodegradable alternatives to the non-biodegradable branched-chained alkylbenzene sulfonates (Gledhill, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…The LAS molecules adsorb to the suspended solid in water bodies and hence end up in sediments along the water course or sludge in treatment plants (Cavalli et al, 2000). The recommended LAS that was claimed by some researcher to biodegrade perfectly (Gledhill, 1974;WHO, 1996 andMcAvoy et al, 1997) have also been reported to poorly degrade in rivers, lakes, ponds and even in soils and this may be toxic to aquatic faunas and floras and can also induce severe damage to vital organs and even haematological, hormonal and enzyme disturbances (Lightowlers, 2004;Ogundiran et al, 2007 andOgundiran et al, 2009). It has also been discovered that detergent surfactant increases microbial populations especially those that are able to use the surfactant as their basic source of carbon or phosphate or both, some of these microorganisms stands as an ectoparasites or endoparasites that causes histological degradation in fish species (Eniola andOlayemi, 2002, andLateef, 2004).…”
Section: Introductionmentioning
confidence: 99%